Aquaponics Aquaculture System as the Most Efficient, Sustainable and Green Aquaculture System: A Review - Mohammed Alhaji , Abbati; Umar Mohammed, Abubakar; Abdulazeez Babayo, Abba; Jesse Aliyu , Jokhtan; Danladi Mohammed, Umar (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Aquaculture in Nigeria has witnessed significant growth and development in recent years, contributing to food security, employment, and economic growth in the country. Aquaponics aquaculture system involves simultaneous used of both hydroponics and fish rearing forms of aquaculture system. Therefore, the end product of this system provides more organic plants and fish species in a manageable environmental condition without affecting the survival, growth and reproduction of other species that are not part of the system. This review aimed at highlighting the efficiency, sustainability and ecologically friendly of aquaponics aquaculture system. Finally, it is reviewed that these systems offer several advantages over conventional farming methods, including efficient nutrient recycling, reduced water usage, and lower environmental impacts. This farming system is devoid of pest and diseases that may likely affect the fish and plant species, it also helps in water conservation, performance increases, stability of food, minimal ecosystem pollution and production at all season. Despite its important and valuable in improving the aquaculture system, it attracts challenges that render it undesirable for all. In Nigeria for example the acceptability of aquaponics system will be limited due to the cost of start- up capital and inadequate technical know-how among our rural community members, Furthermore, It is of paramount important to provide a synergy where local people can access resources for the continued existence of this environmentally friendly system.